Acupuncture or low frequency infrared treatment for low back pain in Chinese patients: a discrete choice experiment - Chen, Li-Chia; Cheng, Li-Jen; Zhang, Yan; He, Zin; Knaggs, Roger (Public Library of Science, 2015)
Acupuncture is a popular but controversial treatment option for low back pain. In China, it is practised as traditional Chinese medicine; other treatment strategies for low back pain are commonly practised as Western medicine. Research on patient preference for low back-pain treatment options has been mainly conducted in Western countries and is limited to a willingness-to-pay approach. A stated-preference, discrete choice experiment was conducted to determine Chinese patient preferences and trade-offs for acupuncture and low frequency infrared treatment in low back pain from September 2011 to August 2012 after approval from the Department of Scientific Research in the study settings. Eight-six adult outpatients who visited the ‘traditional medicine department’ at a traditional Chinese medicine hospital and the ‘rehabilitation department’ at a Western medicine hospital in Guangdong Province of China for chronic low back pain during study period participated in an interview survey. A questionnaire containing 10 scenarios (5 attributes in each scenario) was used to ask participants' preference for acupuncture, low frequency infrared treatment or neither option. Validated responses were analysed using a nested-logit model. The decision on whether to receive a therapy was not associated with the expected utility of receiving therapy, female gender and higher out-of-pocket payment significantly decreased chance to receive treatments. Of the utility of receiving either acupuncture or low frequency infrared treatment, the treatment sensation was the most important attribute as an indicator of treatment efficacy, followed by the maximum efficacy, maintenance duration and onset of efficacy, and the out-of-pocket payment. The willingness-to-pay for acupuncture and low frequency infrared treatment were about $618.6 and $592.4 USD per course respectively, demonstrated patients' demand of pain management. The treatment sensation was regarded as an indicator of treatment efficacy and the most important attribute for choosing acupuncture or low frequency infrared treatment. The high willingness-to-pay demonstrated patients' demand of pain management. However, there may be other factors influencing patients' preference to receive treatments.